2015
DOI: 10.1093/mnras/stv1062
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of the X-ray luminosity functions of unabsorbed and absorbed AGNs out to z∼ 5

Abstract: We present new measurements of the evolution of the X-ray luminosity functions (XLFs) of unabsorbed and absorbed Active Galactic Nuclei (AGNs) out to z ∼ 5. We construct samples containing 2957 sources detected at hard (2-7 keV) X-ray energies and 4351 sources detected at soft (0.5-2 keV) energies from a compilation of Chandra surveys supplemented by wide-area surveys from ASCA and ROSAT. We consider the hard and soft X-ray samples separately and find that the XLF based on either (initially neglecting absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

61
565
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 373 publications
(634 citation statements)
references
References 149 publications
61
565
8
Order By: Relevance
“…We show two simulations, Ref-L100N1504 (dark blue lines) and AGNdT9-L050N0752 (light blue lines). The HXRLF shows strong Green circles correspond to the observational estimates from Miyaji et al (2015), red pentagons to Aird et al (2015) and bright blue hexagons to Buchner et al (2015). Comparing the simulations to each other, we find good agreement at all redshifts with differences no larger than 0.2 dex in normalization.…”
Section: Observable Diagnostics Of Smbh Growthsupporting
confidence: 61%
See 2 more Smart Citations
“…We show two simulations, Ref-L100N1504 (dark blue lines) and AGNdT9-L050N0752 (light blue lines). The HXRLF shows strong Green circles correspond to the observational estimates from Miyaji et al (2015), red pentagons to Aird et al (2015) and bright blue hexagons to Buchner et al (2015). Comparing the simulations to each other, we find good agreement at all redshifts with differences no larger than 0.2 dex in normalization.…”
Section: Observable Diagnostics Of Smbh Growthsupporting
confidence: 61%
“…Ueda et al 2003;Steffen et al 2003) Ueda et al 2014). Because of these uncertainties, we prefer to compare the simulations to observed soft X-ray luminosity functions for which the obscured fraction has already been taken into account by simultaneously fitting to both hard and soft Xray data (Aird et al 2015). In future work, we will investigate the obscuration of AGN due to gas and dust, taking into account the properties of the host galaxy.…”
Section: Predicting X-ray Observablesmentioning
confidence: 99%
See 1 more Smart Citation
“…-) AGN population and further shed light on the known decreasing trend between the numerical relevance of this population compared to all AGN (absorbed fraction) and the source luminosity (Lawrence & Elvis 1982;Gilli et al 2007;Burlon et al 2011;Buchner et al 2015) and its redshift evolution (La Franca et al 2005;Ballantyne et al 2006;Treister & Urry 2006;Aird et al 2015a;Buchner et al 2015;Liu et al 2017). They also allow exploration of the importance of the CT population, although with different constraining power and different non-negligible degrees of bias-especially at the highest column densities and lowest luminosities (e.g., Burlon et al 2011;Brightman et al 2014;Buchner et al 2015;Lanzuisi et al 2015;Ricci et al 2015).…”
Section: Introductionmentioning
confidence: 93%
“…Model predictions from G07, U14, and Aird et al (2015a) are shown in dotted-dashed green, long-dashed orange, and short-dashed blue, respectively. 42 The fraction of the CT sources (relative to all AGN population) obtained with the best-fit slopes is rather high and uncertain, given its large uncertainties; see Table 8.…”
Section: Fraction Of Absorbed Sourcesmentioning
confidence: 99%